Investigating the Relationship between Green Loyalty and Green Behavior on Green Purchase Decisions with the Moderating Effect of Environmental Concerns (Journal of Asian Development Studies, 2024)
The research investigates the effect of Green Loyalty and Green Behaviors on Green purchasing choices, emphasizing the moderating influence of environmental consciousness among consumers of environmentally-friendly fashion, encompassing garments, accessories, and footwear. This complex association was carefully assessed in this study using a survey approach entailing a 16- item questionnaire based on a 5-point Likert scale. More specifically, the selected sample involved customers who belong to the Southern Punjab region. The empirical results further pointed out the importance of both the constructs of green loyalty and green behaviors in making green purchases; however, the environmental concern failed to become an important moderating factor in this regard. By grounding the study in the present environmental context, the research underscores the relevance of green products for present-day business while emphasizing that marketers have to manage two key factors: customer loyalty and behaviors to encourage green buying. This research effort is unique in its attempt to examine green loyalty in relation to green behavior and green buying behavior with special reference to the moderating role of environmental concern.